Design and development of android application for fluid properties ebook and calculator - Khairul Anwar, Zainal Abidin (2013)
Generally, this thesis was about designing and developing an Android application for Fluid Mechanics subject, with the Properties of Fluid subtopic. The main objective was simple, to help students understand Fluid Mechanics subject in the most effective way. This application dealt with colourful simple notes and effectual calculator to bring best out of student's understanding. There had been a number of applications related to Fluid Mechanics subject in Android App Store but it did not match student's need. A simple study was then conducted and the result came out. The prototype version of Fluid Properties was formally launched to get the response among the students and lecturers. The survey did resulting in positive feedback and the final version of the application was then introduced.